Etil-Trinexapac na Cultura da Cana-de-Açucar (Saccharum spp.) - Maia, Messias Selemar (2012)
The use of maturators are becoming a fairly normal habit in the sugarcane industry in Brasil for a faster and even maturation of the cane stalks, especially in the beginning and end of the harvest season, when the stalks are in the vegetative stage with reduced amount of sucrose in the stems. the objective of this study was to evaluate the increment of sugar obtained with the use of chemical ripeners (trinexapac-ethil) in different varieties of sugar cane. The treatments consisted of 0.8 LO.ha-1 of trinexapac-ethil in 6 varieties of sugarcane. The maturator promoved a weight gain of 5.32 kg of total sugar recovered (TSR) pen ton of cane, reaching 11.85 kg of TRS per ton of cane in the variety SP 79-1011, when compared to the control. The use of trinexapac-ethil produced satisfactory results, such as optimization of machines and anticipation of the harvest start and cane grinding by the industry.